Analyzing the relationship between differentiated thyroid cancer and thyroid autoimmunity: an exploratory study from tertiary care center in South India - Hussain, Zahir; Kaharin, Rakesh Chandru; Ayub, Muhamed Faizal; Ferdinant, Jabamalai; Rao, Smitha S. (International Surgery Journal, 2019)
Background: Differentiated thyroid cancer (DTC) is the most common endocrine malignancy. There is a rising incidence of DTC over the past few decades. This dramatic increase in incidence may be due to increased detection rate or because of factors like thyroid stimulating hormone (TSH) or thyroid autoantibodies which remains unclear. Our study aims to analyze the association between DTC and thyroid autoimmunity. Methods: This was a retrospective study over 1 year conducted at the department of endocrine surgery, Madras medical college, a tertiary care center in South India. During the study period, 364 total thyroidectomies were performed which includes 292 benign and 72 malignant cases. Among malignancies, 15 non-DTC cases were excluded from the study. Finally, we included 57 patients with DTC and 114 patients with benign disease (randomly chosen age and sex-matched controls) for analysis. Demographic data, TSH levels, antithyroglobulin (anti-TG), and anti-thyroid peroxidase (anti-TPO) antibody levels, histopathology were recorded and analyzed. Results: Histopathological examination revealed 47.4% of DTC and 63.2% of benign cases has associated thyroiditis. In our study elevated anti-TPO and anti-TG antibodies were not significantly associated with DTC (anti-TPO positivity 75.4% in DTC group vs. 74.6% in benign group, p=0.90, anti-TG antibody positivity 66.7% in DTC vs. 67.5% in benign group, p=0.90). Also, no significant association established between elevated TSH and DTC. Conclusions: Association between thyroid autoantibodies and DTC has been evaluated in several studies with inconsistent results. The present study did not show any significant associations between elevated thyroid autoantibodies, TSH levels, and DTC.